Accuracy of Various Scanning Strategies in Partial Edentulous with Digital Impression - Heny Karni, Riri; Chairunnisa, Ricca; Z Tamin, Haslinda (Indonesia Prosthodontic Association, 2024)
Digital impression of partial edentulous in removable partial denture requires special attention, based on Kennedy's classification, amount of tooth loss and position will affect the accuracy of digital impression. Factors affecting accuracy of intra oral scanner are handling and learning, powdering, lighting, scanning distance, and scanning strategy. The scanning strategy is a certain movement when scanning to improve the accuracy of the virtual model. The accuracy of the scanning strategy in digital impression can be assessed based on trueness and precision. This literature review aims to explain the various scanning strategies on partial edentulous on digital impression accuracy. Most IOS manufacturers recommend specific scanning strategies. In removable partial dentures, it was found that modified scanning strategies were more accurate than the manufacturer's recommended scanning strategies in some clinical situations. For cases in Kennedy Class IV and Class III maxillae the scanning strategy from occlusal to palatal and then to buccal proved to be more accurate. In Kennedy's Class I maxilla, the T-R (Teeth-Ridge) strategy was more accurate than the M (Manufactured) and R-T (Ridge-Teeth) strategies with reduced seesaw effect and high stabilization of the partial removable denture framework. This requires special strategies that depend on the IOS system. The scanning strategy affects the accuracy of digital impression, where the manufacturer's recommended scanning strategy is not necessarily better than the modified scanning strategy. In addition, the location and case of tooth loss also affect the scanning strategy. Key word: strategy scanning, digital impression, trueness, precision, intra oral scanner